PELAKSANAAN PENDIDIKAN ISLAM TERHADAP PERILAKU KEAGAMAAN MASYARAKAT DUSUN SAMPALU KALEDUPA SELATAN KABUPATEN WAKATOBI - Ice Swarmi; Sulasri; Maudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article examines the implementation of Islamic education and its influence on the religious behavior of the community in Sampalu Hamlet, South Kaledupa, Wakatobi Regency. Islamic education within the community functions not only as a process of transmitting religious knowledge but also as a means of fostering religious attitudes in daily life. This study aims to describe the forms of implementation of Islamic education in the community and to analyze its impact on the formation of religious behavior. The research employs a descriptive qualitative approach with a library research design, supported by various written sources such as books, scientific journals, articles, and relevant documents related to Islamic education and community religious behavior, which were analyzed using content analysis techniques. The findings show that the implementation of Islamic education in Sampalu Hamlet is reflected through religious study activities, the habituation of worship practices, the exemplary role of religious leaders, and socio-religious practices integrated into community life. The values of Islamic education that develop include aspects of faith (aqidah), worship (ibadah), morality (akhlak), and social-religious values that gradually shape the community’s religious behavior. Thus, Islamic education functions as an effective non-formal educational medium in fostering religious awareness, strengthening moral values, and sustaining Islamic values in the social life of the local community.Top of FormBottom of Form